The SGLT-2 Inhibitors and their Role in the Treatment of Heart Failure - A Review of Literature - Silvia Ciraolo; Agnieszka Kulczycka-Rowicka; Joanna Wojda; Katarzyna Lesiczka-Fedoryj; Anna Walczak; Zuzanna Kościuszko; Adam Sobiński; Matylda Czerwonka; Katarzyna Kurza; Julianna Podolec (Quality in Sport)
• The purpose of research: Heart failure (HF) is an important global health concern. Despite advancements in treatment, HF remains the leading cause of hospitalization among the elderly. The development of sodium-glucose cotransporter 2 (SGLT2) inhibitors has shown promising cardiovascular and renal benefits beyond glucose control. This study aims to explore the potential mechanisms by which SGLT2 inhibitors provide cardiovascular protection, regardless of type 2 diabetes mellitus (T2DM).